Effects of dielectric barrier discharge on methane/air laminar lean premixed flame - Masashi SUZUKI; Jun HAYASHI; Fumiteru AKAMATSU (Nihon Kikai Gakkai ronbunshu, 2014)
Effects of non-equilibrium plasma on combustion phenomena have been investigated in terms of the improvement of the ignitability and the enhancement of reaction rate of combustion. In this study, effects of dielectric barrier discharge (DBD) on methane/air laminar lean premixed flame were experimentally investigated. It is known that the properties of DBD are affected by characteristics of a power source. To understand effects of the condition of the electric power source of DBD, the peak to peak voltage and frequency of DBD were varied from 10 kV to 36 kV and from 200 Hz to 7 kHz, respectively. Results showed that the length of a lean premixed flame was shortened with DBD. It indicates that the laminar burning velocity was increased. To examine the mechanism of the enhancement of the laminar burning velocity, spectroscopy measurements were performed on the flame with/without DBD conditions. As a result, location of the flame zone, where the chemiluminescence of OH* and CH* was observed, was shifted slightly toward unburned side. In addition, it was found that the chemiluminescence of OH* and CH* steeply increased in a second DBD overlapped with the flame.